![image](https://tex.z-dn.net/?f=%28-6x-1%29%284-5x%29%28x%2B3%29%3E0%2C+%5C%5C%0A-6%5Ccdot%28-5%29%5Ccdot%28x%2B%5Cfrac%7B1%7D%7B6%7D%29%28x-%5Cfrac%7B4%7D%7B5%7D+%29%28x%2B3%29%3E0%2C+%5C%5C%0A30%28x%2B%5Cfrac%7B1%7D%7B6%7D%29%28x-%5Cfrac%7B4%7D%7B5%7D+%29%28x%2B3%29%3E0%2C+%5C%5C%0A%28x%2B%5Cfrac%7B1%7D%7B6%7D%29%28x-%5Cfrac%7B4%7D%7B5%7D+%29%28x%2B3%29%3E0%2C+%5C%5C+%0A%28x%2B%5Cfrac%7B1%7D%7B6%7D%29%28x-%5Cfrac%7B4%7D%7B5%7D+%29%28x%2B3%29%3D0%2C+%5C%5C%0Ax_1%3D-3%2C+x_2%3D-+%5Cfrac%7B1%7D%7B6%7D%2C+x%3D+%5Cfrac%7B4%7D%7B5%7D%2C+%5C%5C+%0Ax%5Cin%28-3%3B-+%5Cfrac%7B1%7D%7B6%7D%29%5Ccup%28%5Cfrac%7B4%7D%7B5%7D%3B%2B%5Cinfty%29)
0, \\
-6\cdot(-5)\cdot(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)>0, \\
30(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)>0, \\
(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)>0, \\
(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)=0, \\
x_1=-3, x_2=- \frac{1}{6}, x= \frac{4}{5}, \\
x\in(-3;- \frac{1}{6})\cup(\frac{4}{5};+\infty)" alt="(-6x-1)(4-5x)(x+3)>0, \\
-6\cdot(-5)\cdot(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)>0, \\
30(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)>0, \\
(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)>0, \\
(x+\frac{1}{6})(x-\frac{4}{5} )(x+3)=0, \\
x_1=-3, x_2=- \frac{1}{6}, x= \frac{4}{5}, \\
x\in(-3;- \frac{1}{6})\cup(\frac{4}{5};+\infty)" align="absmiddle" class="latex-formula">